Pemanfaatan Teknologi Informasi dan Komunikasi Guna Mengendaikan Pola Perilaku Konsumtif Santri Pondok Pesantren Nurul Jadid - Ahmad Febrianto; Roisul Muhtadin; Luthfi Riadi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Information and communication technology that is developing so quickly directly affects the community, including in the world of Islamic boarding schools. Currently, Islamic boarding schools participate in utilizing the development of information technology to improve the quality of their pesantren. The Nurul Jadid Islamic Boarding School in utilizing the rapid development of technology created an E-Bekal program which aims to control the consumptive behavior of students. By using qualitative methods, this research is expected to optimize the use of information technology in order to control the extravagant behavior of the students of the Nurul Jadid Islamic Boarding School in Paiton Probolinggo. The E-Bekal program can regulate the amount of student consumption expenditure, because the program has a maximum daily spending limit of students according to the policies set by the pesantren. With the same maximum limit for all students, the consumptive behavior of students can be controlled so that students do not behave extravagantly. Benefits for guardians of students can make it easier to control the financial expenses of students. and can find out how much they spend each time they make a purchase through notifications sent to their parents through the E-Bekal application installed on Android. You can also find out how much balance is owned by students. Parents (santri's guardians) can top up the balance of the student's provision money through a bank that has been determined by the pesantren.